The Dramatic Works of Gerhart Hauptmann, Volume I - Hauptmann, Gerhart, 1862-1946; Lewisohn, Ludwig, 1882-1955 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Dramatic Works of Gerhart Hauptmann, Volume I" by Gerhart Hauptmann is a collection of plays written during the late 19th century. This volume includes a meticulous selection of Hauptmann's significant social dramas, which explore the lives and struggles of ordinary people, particularly the working class in Silesia. The plays delve into themes of social injustice, class conflict, and the human condition, reflecting the playwright's deep social consciousness and artistic vision. The beginning of this volume introduces the playwright through a preface by Ludwig Lewisohn, detailing Hauptmann's biography, literary influences, and the significance of his work. Following this, the first act of "Before Dawn" unfolds in a rural setting, showcasing a lowly farmer's household. The scene introduces various characters including Krause, his family, and guests, revealing their interactions and social dynamics. Central to the dialogue is the presence of Alfred Loth, an idealistic engineer, who embodies the themes of disillusionment and the pursuit of social progress amid the challenges posed by both personal and societal constraints. This opening effectively sets the stage for Hauptmann's exploration of complex human relationships against the backdrop of a changing society. (This is an automatically generated summary.)
Release date is 2006-02-01
Produced by Charles Aldarondo, Keren Vergon, Thomas Berger and the Online Distributed Proofreading Team
Keywords: German drama -- Translations into English